The modern reception of the best of possible worlds: Notes on the history of philosophy: Kant and Hegel - Cubells, María Ramón (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
In this article, we present the reception that Leibniz’s theory known as the doctrine of optimism had in modernity. Although it is the interpretations of Kant and Hegel that will occupy us, to contextualize the doctrine of the best possible worlds it will be essential to refer to the immediate receptivity that the thesis had in the Enlightenment. Next, we analyze Kant’s text On some Observations about Optimism and his defense of Leibniz’s thesis. We dedicate the last section of the article to the lesson that Hegel devoted to the question of Leibniz’s optimism in his Lectures on the History of Philosophy.